2006
DOI: 10.1007/s00338-005-0080-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of monsoon-driven wave action on coral reefs of Guam and implications for coral recruitment

Abstract: Benthic cyanobacteria can respond rapidly to favorable environmental conditions, overgrow a variety of reef organisms, and dominate benthic marine communities; however, little is known about the dynamics and consequences of such cyanobacterial blooms in coral reef ecosystems. In this study, the benthic community was quantified at the time of coral spawnings in Guam to assess the substrate that coral larvae would encounter when attempting settlement. Transects at 9, 18, and 25-m depths were surveyed at two reef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…1 km) influenced recovery rates as shown by the dominance of certain taxa at particular locations. For instance, Acropora had high coverage at locations with higher water flow while Porites, which is more tolerant to turbid environments, dominated the lo cation near a river, as has been observed in other studies (Storlazzi et al 2005;Becerro et al 2006;Dikou and van Woesik 2006). However, there was also variability between sites at a given location, particularly within locations 3 The structure of coral communities showed the greatest variability on the site scale.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…1 km) influenced recovery rates as shown by the dominance of certain taxa at particular locations. For instance, Acropora had high coverage at locations with higher water flow while Porites, which is more tolerant to turbid environments, dominated the lo cation near a river, as has been observed in other studies (Storlazzi et al 2005;Becerro et al 2006;Dikou and van Woesik 2006). However, there was also variability between sites at a given location, particularly within locations 3 The structure of coral communities showed the greatest variability on the site scale.…”
Section: Discussionsupporting
confidence: 70%
“…If these processes differ on a small spatial scale, patchy distribu tions of corals may arise (van Woesik 2002). Another factor that may cause variation in the recovery process is local environmental conditions on reefs, such as exposure to monsoon winds, strong wave action, and/or the presence of terrestrial inputs (Storlazzi et al 2005;Becerro et al 2006;Dikou and van Woesik 2006).…”
mentioning
confidence: 99%
“…High chemical concentrations in the outer tissues could also be a defense against foulers (6,11). The higher concentration of isofistularin-3 (and other compounds) in the choanosome could be acting as a final deterrent against the specialist predator T. perversa, which is similar to what has been described for other opisthobranchsponge feeding interactions (5,7). Other roles, such as antibacterial activities, are far less investigated but could also explain the observed variation in secondary chemistry (6).…”
Section: Discussionmentioning
confidence: 65%
“…show marked increases in biomass between May (peak settlement for P. astreoides) and August or September (settlement for broadcasting species assayed in the current study). Becerro et al (2006) also suggested that temporal variation in cyanobacterial standing stock may influence the settlement success of mass-spawning corals in Guam.…”
Section: Implications For Reef Restoration Design and Monitoringmentioning
confidence: 99%